2018
DOI: 10.21294/1814-4861-2018-17-4-59-66
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Melanoma Cells Extracted From Different Sites of the Primary Tumor

Abstract: . For citation: Aksenenko M.B., Komina A.V., Palkina N.V., Averchuk A.S., Rybnikov Yu.A., Dyhno Yu.A., Ruksha T.G. transcriptomic analysis of melanoma cells extracted from different sites of the primary tumor. Siberian Journal of Oncology. 2018; 17 (4): 59-66. -doi: 10.21294/1814-4861-2018 Введение. Внутриопухолевая гетерогенность представляет собой характерную черту большинства злокачественных новообразований, в том числе и меланомы кожи. данное свойство является одним из препятствий для проведения эффективн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Long non-coding RNAs control genome integrity, chromatin organization, gene expression, and signal transmission. It has been established and experimentally confirmed that the targeted action of non-coding RNAs on mRNA (in the form of complementary antisense oligonucleotides) can alter the expression levels of target genes [ 11 ].…”
Section: Role Of Mirnas In Epigenetic Regulation Of Genome Translationmentioning
confidence: 99%
“…Long non-coding RNAs control genome integrity, chromatin organization, gene expression, and signal transmission. It has been established and experimentally confirmed that the targeted action of non-coding RNAs on mRNA (in the form of complementary antisense oligonucleotides) can alter the expression levels of target genes [ 11 ].…”
Section: Role Of Mirnas In Epigenetic Regulation Of Genome Translationmentioning
confidence: 99%